Study of Air Velocity and Temperature Gradient in Lecture Room Through Mixed and Displacement Ventilation Systems to Improve the Thermal Comfort - Bambang Iskandriawan (IPTEK The Journal for Technology and Science, 2010)
Air ventilation system is considered crucial in the target of maintaining clean and fresh room air at all times. It will improve the thermal comfort and indoor air quality along with the activities of occupant. This investigation explores the influence of fresh air diffuser location to the thermal comfort factor especially in the lecture room. It will contrast two types of ventilation: the mixed and the displacement ventilation. The thermal comfort factor is represented by means of air velocity and temperature. Using Fluent 6.2 as CFD (Computational Fluid Dynamics) simulation program, all the variables will be exploited. The specific boundary type’s room model is verified in GAMBIT software generating such a specific lecture room. The finding shows that the displacement ventilation system has benefit in the propensity of controlling the heat and air velocity compare to the mixed ventilation